A gigantic deep-sea Nucinellidae from the tropical West Pacific (Bivalvia: Protobranchia) - la Perna, Rafael (Zootaxa, 2005)
Nucinella boucheti n. sp. is described from a 1610–1580 m deep station in the Philippines (Musorstom 2 Expedition). Nucinellids are typically small, mostly not exceeding 5 mm, but the present species is 25 mm large, being by far the largest nucinellid so far known. The adaptive meaning of this case of gigantism remains open to speculation, but it may be an expression of a rapid diversification of the Holocene nucinellids. Nucinella boucheti n. sp. has numerous, thin and delicate subumbonal teeth, displaying a number of unusual shapes and contrasting with the few, rather coarse and stout teeth of the other nucinellids. This feature is believed to be due to allometric constraints related to the large size. With N. boucheti, 19 living species of nucinellids are known, 14 of which belonging to the genus Nucinella. The Central West Pacific, from Japan to South Australia, is the area with the maximum diversity of nucinellids (11 species).